The role of plant hormones during grafting - Nanda, Amrit K.; Melnyk, Charles W. (Journal of plant research, 2018)
For millennia, people have cut and joined different plant tissues together through a process known as grafting. By creating a chimeric organism, desirable properties from two plants combine to enhance disease resistance, abiotic stress tolerance, vigour or facilitate the asexual propagation of plants. In addition, grafting has been extremely informative in science for studying and identifying the long-distance movement of molecules. Despite its increasing use in horticulture and science, how plants undertake the process of grafting remains elusive. Here, we discuss specifically the role of eight major plant hormones during the wound healing and vascular formation process, two phenomena involved in grafting. We furthermore present the roles of these hormones during graft formation and highlight knowledge gaps and future areas of interest for the field of grafting biology.